2019
DOI: 10.2478/jwld-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the impact of design rainfall on the urban drainage system by Storm Water Management Model

Abstract: Flood modelling is an effective way to manage the stormwater network in cities. It aims to understand and predict the behaviour of stormwater network so that it can test and evaluate effective solutions to structural and operational problems. So simulation modelling stays a preoccupation for building a successful hydraulic modelling in urban areas. This study investigates the impact of the design rainfall on the hydraulic modelling results for the Azzaba stormwater network located in the North-East of Algeria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The simulations showed that the more rainfall intensity increases, the greater the extent of flooding, and consequently resulting in an increase in water depth at the outlet. This finding corroborates the results obtained by Laouacheria et al [57], where the impact of the designed rainfall was investigated using hydraulic tools based on the complete Saint-Venant equations within the Storm Water Management Model (SWMM).…”
Section: Discussionsupporting
confidence: 90%
“…The simulations showed that the more rainfall intensity increases, the greater the extent of flooding, and consequently resulting in an increase in water depth at the outlet. This finding corroborates the results obtained by Laouacheria et al [57], where the impact of the designed rainfall was investigated using hydraulic tools based on the complete Saint-Venant equations within the Storm Water Management Model (SWMM).…”
Section: Discussionsupporting
confidence: 90%
“…As well as to find and determine the right drainage system. Other studies have analyzed similar problems using SWMM and Rational Method [4], [5], [6], [7], [8], [9], [10], [11], [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the modelling of flash floods, previous studies used various physical or statistical models to provide precise mapping for flood-prone zones. Physical models include the Hydrological Simulation Program-FORTRAN (HSPF) [12], Storm Water Management Model (SWMM) [13], and HEC-RAS [14,15], while statistical models include logistic regression, generalized linear models, entropy, frequency ratio (FR), Random Forest (RF), k-nearest neighbours (KNN), weighting factors, weights of evidence, and flexible discriminant analysis [16,17]. These models can be used to determine the connections between the location of an FSM-appropriate or inappropriate area and its conditioning elements.…”
Section: Introductionmentioning
confidence: 99%